The role of Institutionalization in the leadership style of Imam Khomeini - Zahed GHAFARI HASHJIN; Ghodsi Alizadeh Saylab; Yosef Torabi (Islām va ̒ulūm-i ijtimā̒ī, 2021)
The aim of this study is to investigate and explain institutionalization in Imam Khomeini's political thought and practice. In order to answer the research questions, document analysis (a qualitative method) was used. With this method, available documents including books, articles and theses were reviewed. By examining the political thought of Imam Khomeini, it was found out that factors such as “paying attention to social values”, political crises”, and “temporal conditions” were effective in his institutionalization. It can be said that institutionalization has a special role in Imam Khomeini's political thought and practice. After examining his political thought, it was tried to provide evidences of institutionalization done by Imam Khomeini based on various functions and with regard to the above mentioned factors. Results showed that presenting and introducing political, legislative, judicial, scientific, cultural, military and service institutions, periodically and permanently, are the evidences of institutionalization under the leadership of Imam Khomeini.